E-Human Resource Management: A Case Study of the State Bank in Pakistan - Zafar, Junaid (2009)
The knowledge-intensifying process of the economy and the correlated rise of organizational networks, with their greater dependency on qualified and committed employees, explain the need for a form of Human Resource Management that meets the demands and needs of the management and the employees of the network organization. Considering this, the requirements for such a form of HRM that become apparent are: online applications for HR information, and the tools that are available at any time in any place, and that enable continuous interaction between the employees and the organization.The software industry has developed for the HR personal to make it able to store, sort and retrieve information placed on huge databases. e-HR is the actually a strategic iniative to make the organization propel itself in the information age; by freeing itself from daily operational, monotonous requirements and making it more in tune with the decision making and better understanding of the employees. With the increasing possibilities of providing services to employees and management through Internet and Intranet applications, an HR professional would not be necessary to obtain information form HR policies and practices with in an organization. E-Human resource Management is emerging; it is knocking on the doors of HR departments and even entering without asking. In organizations managerial boards are aware, but little is being done. The research is focused on Pakistan. It is a strategically important country with lots of foreign capital being invested in the country.